Military waste the unexpected consequences of permanent war readiness - Reno, Joshua (University of California Press, 2019)
"World War III never happened, and yet material evidence of this contest is strewn everywhere: resting at the bottom of the ocean, rusting in deserts, orbiting Earth. Military Waste examines the lives and stories of American civilians confronted with what is left over and cast aside when a society is permanently ready for war. They encounter risks and opportunities that manifest whether or not any specific war ever takes place, questioning what led to the largest military the world has ever seen and pondering what will become of its remains"--Provided by publisher